Power and performance analysis of UUV motor systems with torpedo capabilities using to support the indonesian navy's maritime operations - Gustav Irgi Aldhiantoro; Kuntjoro Pinardi; Adhi Kusumadjati; Annisa Mutiara Putri Abdul; Dinda Rahma Dewi; Moh. Hisni Alfan Baarik; Endah Kinarya Palupi (FoundAE, 2025)
Unmanned Underwater Vehicles (UUVs) play a crucial role in modern naval operations, particularly in Intelligence, Surveillance, and Reconnaissance (ISR) and Anti-Submarine Warfare (ASW). Their stealth and long-range capabilities provide strategic advantages, yet extended missions pose significant challenges due to power limitations. This study proposes a novel approach to predicting and managing UUV battery capacity for missions lasting up to 30 days. Utilizing OpenModelica, we simulate various operational scenarios by modeling the Direct Current Permanent Magnet (DCPM) motor and its interaction with propulsion systems under different mission profiles including patrol, standby, and attack phases to estimate power consumption and optimize endurance. The results demonstrate key strategies for enhancing UUV autonomy and operational flexibility through advanced power management. These findings contribute to the development of more efficient UUV systems capable of prolonged underwater missions with minimal recharging.